2014
DOI: 10.1002/14651858.cd009076.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating femoral shaft fractures in children and adolescents

Abstract: Interventions for treating femoral shaft fractures in children and adolescents (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…Complication rates after ESINF have been associated with the severity of the comminution and the fracture stability . In our study, neither the extent of the comminution nor the fracture pattern had a significant association with loss of reduction or malunion in the ESINF group.…”
Section: Discussioncontrasting
confidence: 63%
“…Complication rates after ESINF have been associated with the severity of the comminution and the fracture stability . In our study, neither the extent of the comminution nor the fracture pattern had a significant association with loss of reduction or malunion in the ESINF group.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, the low mean age of participants (4.2 ± 3.3 years), the low rate of associated injuries (4/29 children) and the high proportion of closed simple diaphyseal non displaced fractures (23/30 cases) were already highly suggestive that there should be greater indication of a conservative approach in fracture management. Although with low quality evidence, a recent meta-analysis of randomized controlled trials concluded that compared to conservative treatment, elastic intramedullary nailing may shorten rehabilitation time [5]. The benefits of a speed up recovery cannot be over emphasized, given our observed longer durations of immobilization (p < 0.0001) and consolidation (p < 0.0001) in school-aged children compared to preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a recent systematic review of randomized controlled trials did not ascertain the efficacy of conservative management over surgical management of femoral shaft fractures and vice versa, in terms of long-term functional outcome [5]. The choice between conservative and surgical treatment has traditionally been multifactorial, influenced by age and weight of the child, associated injuries, the fracture characteristics, institutional or surgeons' preferences, economic and social concerns [5-7]. Due to rapid bone remodelling, most of the femoral fractures in children younger than six years can be managed conservatively by traction and plaster-cast immobilization [8].…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic management of pediatric femur fractures is variable depending on patient age, fracture characteristics, and available resources. 1 These fractures can cause significant bleeding into the thigh, requiring emergent traction and splinting to reduce intravascular blood loss. Pain management in this setting can be challenging because quadriceps muscles tend to spasm during patient movement, resulting in marked increases in pain.…”
Section: Learning Objectivesmentioning
confidence: 99%